A Cross-Sectional Assessment of Bacterial Contamination in Fixed Prosthodontic Impressions Transferred from Clinics to Dental Laboratories: A Study in Tripoli, Libya (Razi Medical Journal, 2025)
Fixed prosthodontic impressions are essential in restorative dentistry but pose significant cross-contamination risks if inadequately disinfected, with adherence to protocols being particularly low in developing regions like Libya. This cross-sectional study evaluated bacterial contamination of 100 fixed prosthodontic impressions arriving at a central dental laboratory in Tripoli, collected from 23 private clinics, aiming to determine the prevalence and pathogenicity of implicated bacterial species. Microbiological analysis utilised selective and differential culture media under aerobic and anaerobic conditions, with isolates identified through colony morphology, Gram staining, and microscopic examination. Identified strains were classified as pathogenic, potentially pathogenic, or non-pathogenic, and the antibiotic susceptibility of pathogenic isolates was tested via Kirby-Bauer disk diffusion. Results revealed a high contamination rate, with 90% of impressions harbouring bacteria. Twenty-one bacterial species were identified, with pathogenic bacteria being predominant; Escherichia coli (13%), Streptococcus pyogenes (11%), and Staphylococcus aureus (9%) were the most common. Statistical analysis (Kruskal-Wallis test and Dunn-Bonferroni post-hoc tests) indicated significant differences in contamination rates between bacterial groups (*p* = 0.009), confirming pathogenic bacteria were significantly more prevalent than potentially pathogenic strains. The extensive prevalence of pathogenic microbes indicates a critical failure in current infection control practices within the sampled clinics. The urgent implementation of standardized disinfection protocols is essential to protect both laboratory personnel and patients' health. Future studies must examine the efficacy of diverse disinfection procedures and elucidate the molecular survival mechanisms of microbes on impression materials.
Keywords: Fixed Prosthodontic Impressions, Bacterial Contamination, Infection Control, Pathogenic Bacteria, Disinfection Protocols, Tripoli, Libya.